2023
DOI: 10.1111/avsc.12718
|View full text |Cite
|
Sign up to set email alerts
|

Grazing by semi‐feral cattle and horses supports plant species richness and uniqueness in grasslands

Abstract: Question: How does naturalistic grazing (trophic rewilding with large herbivores), in contrast to mowing and free succession (no grazing), affect plant community composition and species richness in temperate grassland grazed by semi-feral cattle and horses?Location: Mols Laboratory, Denmark. Methods:We investigated grazing exclosures in the rewilding area of the Mols Laboratory, four years after its establishment. We focused on moist to dry grassland vegetation, that is, excluding scrub and woodland. Each expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results indicate that, contrary to some earlier findings (e.g., Eldridge et al, 2019) and the concerns of conservation managers, multi-species grazer assemblages in close-to-natural (i.e. 0.3-0.4 animals per ha) densities do not have a destructive impact on herbaceous plants, but are rather an effective tool in conservation management, in line with recent findings (Bonavent et al, 2023).…”
Section: Discussionsupporting
confidence: 84%
“…Our results indicate that, contrary to some earlier findings (e.g., Eldridge et al, 2019) and the concerns of conservation managers, multi-species grazer assemblages in close-to-natural (i.e. 0.3-0.4 animals per ha) densities do not have a destructive impact on herbaceous plants, but are rather an effective tool in conservation management, in line with recent findings (Bonavent et al, 2023).…”
Section: Discussionsupporting
confidence: 84%
“…Our findings show that European forests included substantial open and light woodland elements and suggest an important role for processes that maintain open habitats. This may have important implications for European biota and particularly for rarer species that depend on open, intermediate, and disturbed landscapes ( 54 , 55 ). Consequently, common approaches to restoration, such as tree planting, risk creating unfavorable habitats for biodiversity that has evolved in heterogeneous landscapes ( 5 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…As trophic rewilding is a young field the number of empirical studies on self-identified rewilding efforts remains limited, albeit strongly rising (Svenning et al, 2016;Hart et al, 2023). However, there are many empirical studies on the ecosystem effects and biodiversity outcomes of de facto trophic rewilding, especially in Europe, North America, and southern Africa, often under names such as year-round or extensive grazing, or reintroductions, e.g., with many showing positive biodiversity effects (especially for plants) attributable to bison (e.g, Ratajczak et al, 2022) or feral and semiferal cattle and horses (e.g., Konvička et al, 2021;Dvorský et al, 2022;Bonavent et al, 2023;Köhler et al, 2023). Further, several long-term cases of megafauna recovery that did not necessarily emerge out of rewilding principles show how trophic rewilding can result in largescale top-down effects on ecosystems, for example vegetation changes in response to the reestablishment of white rhinoceros (Ceratotherium simum) (Cromsigt and te Beest, 2014) and African savanna elephants (Gordon et al, 2023).…”
Section: Megafauna-based Trophic Rewilding As a Restoration Approachmentioning
confidence: 99%